HX008, an anti-PD1 antibody, plus irinotecan as second-line treatment for advanced gastric or gastroesophageal junction cancer: a multicenter, single-arm phase II trial - Ning Li; Shu Zhang; Yan Song; Jing Huang; Qun Li; Xinjun Liang; Qingxia Fan; Xianli Yin; Zhixiang Zhuang; Yunpeng Liu; Jingdong Zhang; Xiaoge Kou; et al. (Journal for ImmunoTherapy of Cancer)
Background Irinotecan is used as second-line treatment in advanced gastric or gastroesophageal junction (G/GEJ) cancer. The role of anti-programmed death-1 (PD-1) antibody plus irinotecan, in this setting and population is unclear.Methods This multicenter, open-label, single-arm, phase II trial was conducted in 11 Chinese hospitals. Eligible patients had histologically confirmed advanced G/GEJ cancer that refractory to, or intolerant of, first-line chemotherapy with a platinum and/or fluoropyrimidine. Subjects received HX008 200 mg intravenously every 3 weeks plus irinotecan 160 mg/m2 intravenously every 2 weeks until disease progression or unacceptable toxicity. The primary end point was objective response rate (ORR) as assessed according to Response Evaluation Criteria In Solid Tumors V.1.1.Results Between October 2018 and September 2019, a total of 58 patients with advanced G/GEJ cancer were enrolled in this study. Median follow-up was 10.5 months (range 7.4–18.9) months. Confirmed ORR was observed in 16 patients, for an ORR of 27.6% (95% CI 16.1% to 39.1%); 19 patients experienced stable disease, leading to a disease control rate of 60.3% (95% CI 46.4% to 73.0%). ORR in patients with PD-ligand 1 (L1) positive (Combined Positive Score (CPS) ≥1) and negative (CPS＜1) tumors was 38.5% (5/13) and 37.5% (3/8), respectively. Median duration of response was 8.0 months (range 1.5–12.5), 6 of 16 (37.5%) responses were ongoing. Median progression-free survival (PFS) was 4.2 months (95% CI 2.2 to 5.5). Median overall survival (OS) was not reached (NR) (95% CI 8.7 to NR). Patients with PD-L1 positive tumors tended to have longer OS than those with PD-L1 negative tumors, but the difference was not statistically significant (NR vs 8.7 months, p=0.1858).The most common treatment-related adverse events of grade 3 or 4 included neutropenia (32.8%), leukopenia (31.0%), anemia (17.2%), decreased appetite (8.6%), vomit (6.9%), nausea (6.9%) and fatigue (5.2%). There were no treatment-related deaths.Conclusion The combination of HX008 and irinotecan demonstrated promising activity and manageable safety as second-line treatment in patients with advanced G/GEJ cancer, which warrants further study.Trial registration number NCT03704246